Characterization of lactic acid bacteria isolated from stinky tofu and suan-tsai using API 50 CHL - Budiatmoko, Aurelia Wibowo; Wulandari, Dyah; Hwang, Chin-Fa; Budiharjo, Anto -; Prayogo, Fitra Adi (Bioma : Berkala Ilmiah Biologi, 2025)
Stinky tofu and suan-tsai are traditional Taiwanese fermented foods produced through spontaneous fermentation involving lactic acid bacteria (LAB). This study aimed to explore the diversity of lactic acid bacteria present in suan-tsai and stinky tofu through the isolation, characterization, and identification of bacterial strains based on characteristics and the API 50 CHL Kit with 16S rRNA gene sequencing considered for future confirmation. Samples were diluted and cultured on MRS agar with the addition of CaCO₃. The 20 colonies forming clear zones were selected for morphological and biochemical characterization including microscopy, gram staining, motility, and catalase activity. Two isolates exhibiting clear zone formation, Gram-positive staining, non-motile behavior, cocci or rod-shaped morphology, and negative catalase activity were selected for identification using the API 50 CHL test kit. One isolate from stinky tofu (A11) was identified as Leuconostoc mesenteroides with 99.8% similarity and, one isolate from suan-tsai (C9) was identified as Lactobacillus casei with 99.4% similarity. Both strains were gram-positive, non-motile, and catalase-negative, indicating LAB characteristics. L. mesenteroides is a heterofermentative bacterium that produces lactic acid, CO₂, and ethanol contributing to creating an acidic condition and flavor development. L. casei is a homofermentative bacterium that support maintenance of low pH, inhibits pathogenic microorganisms, and supports food preservation. The probiotic potential of these strains was based on literature reports describing the antimicrobial and health promoting properties. These findings highlight representative LAB from Taiwan traditional fermented foods and its potential role in preservation, quality, and functionality.